The Neoproterozoic Ceará Group, Ceará Central domain, NE Brazil: Depositional age and provenance of detrital material. New insights from U–Pb and Sm–Nd geochronology. (March 2015) - Arthaud, M.H.; Fuck, R.A.; Dantas, E.L.; Santos, T.J.S.; Caby, R.; Armstrong, R.
Abstract: From the Archean to the end of the Neoproterozoic the Borborema Province, northeast Brazil went through a complex polycyclic geologic evolution, ending, between 660 and 570 Ma, with the Brasiliano/Pan-African orogeny that led to West Gondwana amalgamation. Evolution of the metasedimentary covers of the Province, from the beginning of their deposition up to their involvement in the Brasiliano/Pan-African collision, is a key element in understanding formation of Gondwana and in attempts in pre-drift correlation between South America and West Africa. One of these covers, the Ceará Group, is exposed in the Ceará Central domain. Aiming to unravel the history of the Ceará Group, we carried out a geochronologic study of representative samples, combining Sm–Nd isotopic data, conventional U–Pb TIMS dating of zircon and U–Pb SHRIMP age determination of detrital zircon grains. Our results show that sedimentation of the Ceará Group started around 750 Ma, following rifting of the Archean/Paleoproterozoic basement, associated with bimodal volcanism. The interlayered basic volcanic rocks, re-crystallized into garnet amphibolites, show a concordant age of 749 ± 5 Ma interpreted as the age of crystallization. About 90% of calculated Sm–Nd TDM model ages of metasedimentary rocks are Paleoproterozoic and more than 50% of the analyzed samples have TDM between 1.95 and 2.4 Ma, with strongly negative ɛ Nd, consistent with provenance mainly from the Paleoproterozoic basement. Strong contrast between Paleoproterozoic TDM with negative ɛ Nd and young TDM (Mesoproterozoic) with slightly positive ɛ Nd is interpreted as a consequence of changes in detritus provenance induced by geomorphologic alterations resulting from tectonic activity during rifting. Ages of detrital zircon grains obtained by SHRIMP U–Pb analyses show three main groups: about 1800 Ma, 1000–1100 Ma and ca. 800 Ma which corresponds to the bimodal magmatism associated, respectively to the Orós-Jaguaribe domain, Cariris Velhos event and Independência Group. Highlights: Provenance study Sm–Nd and U–Pb SHRIMP from the metasedimentary rocks of the Ceará Central domain. Neoproterozoic deposition event related to the West Gondwana amalgamation in the north portion of the Borborema Province. Neoproterozoic mafic magmatism in the Ceará Central domain.